Respostas
respondido por:
4
Equação da circunferência
![\boxed{(x-a)^2+(y-b)^2=r^2} \boxed{(x-a)^2+(y-b)^2=r^2}](https://tex.z-dn.net/?f=%5Cboxed%7B%28x-a%29%5E2%2B%28y-b%29%5E2%3Dr%5E2%7D)
Agora, podemos fazer assim:
![-a = -3\\\\ \boxed{a=3}\\\\\ -b=-2\\\\ \boxed{b=2}\\\\ r^2=16\\\\ \boxed{r=4} -a = -3\\\\ \boxed{a=3}\\\\\ -b=-2\\\\ \boxed{b=2}\\\\ r^2=16\\\\ \boxed{r=4}](https://tex.z-dn.net/?f=-a+%3D+-3%5C%5C%5C%5C+%5Cboxed%7Ba%3D3%7D%5C%5C%5C%5C%5C+-b%3D-2%5C%5C%5C%5C+%5Cboxed%7Bb%3D2%7D%5C%5C%5C%5C+r%5E2%3D16%5C%5C%5C%5C+%5Cboxed%7Br%3D4%7D)
Portanto, o Centro é C(3,2) e o raio é 4.
Agora, podemos fazer assim:
Portanto, o Centro é C(3,2) e o raio é 4.
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás